Qualidade de hortaliças não convencionais minimamente processadas - Resende, Nathane Silva (2018)
The unconventional vegetables, for the most part, are rustic vegetables with little commercial appeal. They present high nutritional and functional potential, being sources of vitamins, minerals, phenolic compounds and fibers. Due to urbanization, the market has in a way restricted the number of species available, giving preference to vegetables with already established productive chain, so the consumption of several species has fallen into disuse. The inclusion of unconventional vegetables in food contributes not only to the individual's nutrition, but also to ensure the preservation of local and regional gastronomic richness.The minimally processed products have a market in great expansion and are the focus of countless researches, this because they unite the practicality without losing the freshness and nutritional quality of fruits and vegetables. Thus, the present work has the objective of studying the quality of three unconventional vegetables (azedinha - Rumex acetosa L., ora-pro-nóbis - Pereskia aculeata Mill. And taioba - Xanthosoma sagittifolium) minimally processed. The results of the research indicate that the minimum processing of unconventional vegetables can be an excellent alternative for the insertion of this food group in the consumer's table, thus increasing the commercial value of this product and, consequently, increasing the income of family farmers and trade local. In addition, the consumption of unconventional vegetables is capable of supplying a series of nutritional deficiencies of the population in general, mainly of the most needy populations.